Reasons for interruptions at work: Illuminating the perspective of the interrupter - Leon Toebben; Anne Casper; Wilken Wehrt; Sabine Sonnentag (Journal of Organizational Behavior, 2024)
Summary This research sheds light on two crucial yet overlooked aspects of work interruptions: the perspective of employees who initiate interruptions and the reasons behind those interruptions. Building on earlier research on interruptions and theories on employee motivation, we identified six key reasons for interruptions that we integrated into a typology. This typology combined three interruption topics (performance, belongingness, and hedonic well-being) and two interruption foci (benefitting the interrupter and benefitting the interruptee; i.e., self-focused and other-focused). We validated this typology using qualitative reports and a scale-development approach, thereby creating the interruption-for-a-reason scale (IFRS). We found that interruptions were typically initiated for good reasons and positively correlated with social exchange constructs. That is, initiating interruptions was linked to requesting social support and to performing prosocial behaviors to coworkers. Altogether, this research contributes to a more comprehensive understanding of interruptions by offering a new perspective on interruptions that addresses the complexities of this phenomenon. Illuminating the interrupters' perspective and the various reasons for interruptions is key to a more balanced examination of the positive and negative aspects of interruptions.
Keywords: 330; scale development; social exchange; validation; work interruption